2023
DOI: 10.1101/2023.10.23.23297420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treatment planning for photodynamic therapy of abscess cavities using patient-specific optical properties measured prior to illumination

Zihao Li,
Md Nafiz Hannan,
Ashwani K. Sharma
et al.

Abstract: Background: Photodynamic therapy (PDT) is an effective antimicrobial therapy that we used to treat human abscess cavities in a recently completed Phase 1 clinical trial. This trial included pre-PDT measurements of abscess optical properties, which affect the expected light dose to the abscess wall and eventual PDT response. Purpose: The objective of this study was to simulate PDT treatment planning for the 13 subjects that received optical spectroscopy prior to clinical abscess PDT. Our goal was to determine t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…In prior retrospective studies, we have shown the importance of this for improving eligibility for PDT 25,26 . Further, the optical properties reported here have been used to generate retrospective treatment plans for the 13 subjects that received both PDT and spectroscopy 24 . In particular, the effects of abscess wall absorption have a pronounced effect on generated treatment plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior retrospective studies, we have shown the importance of this for improving eligibility for PDT 25,26 . Further, the optical properties reported here have been used to generate retrospective treatment plans for the 13 subjects that received both PDT and spectroscopy 24 . In particular, the effects of abscess wall absorption have a pronounced effect on generated treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the first report on the optical properties of human abscess cavities, as well as the retention of MB following a 10 minute incubation. These optical property measurements set the stage for patient-specific treatment planning 24 , building on our retrospective study results 25,26 . We previously reported preliminary results for the first three subjects measured in this study 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial inter-patient variability in the abscess wall optical properties was found [5]. We have shown that patient-specific treatment planning incorporating knowledge of these optical properties greatly improves delivery of an efficacious fluence rate to the abscess wall [6,7]. Measurement of individual patient optical properties is therefore of high importance for the clinical success of PDT for this application.…”
Section: Introductionmentioning
confidence: 99%